Lelkészeknek – a lelkészkép – lelkészi identitás kérdése az önértelmezésünk rögös útján – - KOCSEV, Miklós (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
The Problem of Self-image and Identity by Pastors. The problem of self-image and identity is an issue that seems to trouble theologian more and more, but pastors less and less. Every related person agrees mainly that fundaments regarding this must be respected, since the heritage of Reformation for a Reformed pastor is indispensable. It is commonly known that the Reformation had a huge contribution to the interpretation of the church offices, and of the pastor’s office. But of course it could not deal with all that troubles contemporary pastors, namely with the problem of identity and self-interpretation of pastors. The study deals with the problem of the 21st century development of the pastor-image, taking in consideration that this image is shaped by several internal and external factors. In my opinion, the topic is important not only outside our borders, but also in the Carpathian basin. Questions are not fully answered in this paper. We try only to wake the interest to think further the topic. We do this based on the book of Gábor Hézser: Pasztorálpszichológiai szempontok az istentisztelet útkereséséhez, choosing from it several sentences that are developed in this paper.